2007
DOI: 10.1007/s00180-007-0072-x
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian spatial modeling of genetic population structure

Abstract: Bayesian inference, Genetic structure, Spatial modeling, Statistical learning theory, Unsupervised classification,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
340
0
15

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(357 citation statements)
references
References 23 publications
2
340
0
15
Order By: Relevance
“…In the original methods developed by Pritchard et al (2000), Dawson and Belkhir (2001) and Corander et al (2003), spatial information was not explicitly included in the modeling. However, some recent Bayesian assignment methods incorporate information from the geographical coordinates of individuals, by using prior distributions for the spatial distribution of individuals in a cluster (Wasser et al, 2004;Guillot et al, 2005;François et al, 2006;Corander et al, 2008). Simulation studies have shown that incorporation of geographical information into assignment methods can result in better statistical performance (Chen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the original methods developed by Pritchard et al (2000), Dawson and Belkhir (2001) and Corander et al (2003), spatial information was not explicitly included in the modeling. However, some recent Bayesian assignment methods incorporate information from the geographical coordinates of individuals, by using prior distributions for the spatial distribution of individuals in a cluster (Wasser et al, 2004;Guillot et al, 2005;François et al, 2006;Corander et al, 2008). Simulation studies have shown that incorporation of geographical information into assignment methods can result in better statistical performance (Chen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To examine if the resulting genetic structure was correlated with geographical distribution, Mantel's tests were performed with GenAlEx 6.5 (10 permutations). Moreover, a spatial Bayesian clustering algorithm was applied using BAPS 5.2 (Corander et al 2008;Cheng et al 2013) and performing 10 independent runs for each lvalue (1-20). The resulting partitions were visualized as Voronoi diagrams (tessellations).…”
Section: Genetic Structurementioning
confidence: 99%
“…Bayesian identification of genotype pools in U. laevis Two Bayesian clustering programs were used to assess population structure in the microsatellite data set: STRUCTURE v.2.1 (Pritchard et al, 2000) and BAPS v.4.0 (Corander et al, 2008). First, we used STRUCTURE to reveal individualbased patterns in genetic variation without prior information on sample geographic origin.…”
Section: Dna Extraction and Scoring Of Molecular Markersmentioning
confidence: 99%